Effects of social support and self-efficacy of glucose control among Malaysian type 2 diabetes mellitus patients in primary care - Abdul Rashid, Aneesa; Hamzah, Zuhra; Tan, Chai Eng; Devaraj, Navin Kumar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Diabetic control depends partially on self-management. Diabetes self-care is reported to be a strong predictor of glycemic control in Type 2 Diabetes Mellitus (T2DM) patients. Factors contributing to better self-care include self-efficacy and social support. We aim to determine effects of these factors on glucose control in T2DM patients in a primary care clinic. Methods: This study utilised data from a bigger study looking into factors affecting social support and self-efficacy and their correlation in T2DM patients. This study was done among 329 T2DM patients attending a primary care clinic in Selangor, Malaysia between November 2013- January 2014. Systematic random sampling was used. Instruments used were the MOS Social Support Survey and the Diabetic Management Self Efficacy Scale (DMSES). Patients’ socio-demographic data and glucose monitoring records were obtained. The association between social support and self-efficacy with blood glucose control was determined using logistic regression. Results: The mean age of the respondents is 54.6 (+11.2), mostly female (55.3%) and Malay ethnicity (63.5%). Being older and retired were predictors for good glucose control (OR=1.05,p=0.01 and OR=2.2,p=0.023) respectively. There is also significant correlations between number of close friends/relatives with social support and self-efficacy (r=0.162,p=0.030 and r=0.190,p=0.01) respectively. The correlation of social support and self-efficacy with HbA1c levels are r= -0.044(p=0.426) and r= -0.08(p= 0.744) respectively. Conclusion: There were no correlations between social support and self-efficacy with the level of HbA1c among patients with T2DM in this study. We found older aged and retired patients to have better HbA1c levels.